Considerations in the use of work-from-home (WFH) for post-pandemic planning and management - Manko, Barbara A. (Zielona Góra: Faculty of Economics and Management Press)
After widespread use of work-from-home (a.k.a. `remote work`) during the COVID-19 pandemic, many organizations intend to continue or expand its use into the future. This paper presents a literature review and results from an original survey, both of which point to key considerations for planners and managers. Subjects that are highlighted include: giving remote workers access to job-related information they need; recognizing that certain types of tasks may be more challenging to manage in WFH, such as loosely specified tasks and those involving substantial change or newness; and issues that arise in regard to morale and motivation.
Keywords: work-from-home; WFH; remote work; post-pandemic management; post-lockdown management; giving access to information; praca zdalna; praca z domu; pandemia; lockdown; organizacja pracy; dostęp do informacji